Digital Tools for Evaluation: Exploring the Efficacy of Quizizz and Google Forms in Assessing Student Grammar - Zaidaan, Arkaan; Aliyayahya, Fera; Wijaya, Shalu Azzahra; Fadillah, Hafizh; Syauki, Syauki (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
There are many online learning media to be learned such as Quizizz and Google Forms. This research is motivated by the pressing need to explore effective approaches to English language instruction and the potential between Quizizz and Google Forms as educational technologies to revolutionize the assessing process. The purpose of this research is to explore the use of Quizizz and Google Forms as assessment tools for measuring grammar. This research uses a Qualitative Method by giving ten students questionnaires, a grammar question in a Quizizz, and a grammar question in Google Forms to analyze the differences in student performances and understanding between using Quizizz and Google Forms. Based on the research results, Google Forms is more suitable for online questionnaires, surveys, and quizzes used by lecturers, students, and professors. On the other hand, Quizizz is more suitable for combining learning and playing. Quizizz is also more suitable for increasing student learning motivation.